A Multidimensional Assessment of Ethical Codes: The Professional Business Association Perspective - Tucker, Lewis R. (Journal of business ethics, 1999)
This article develops a multidimensional approach for the investigation of the ethical codes of professional associations. The authors: (a) examine various ethical frameworks to identify ethical constructs, (b) select ethical constructs to apply to the assessment of professional codes of ethics, (c) content analyze conceptual and descriptive similarities and differences across a large sample of professional codes of ethics, (d) address organizational variables that affect the development of ethical codes, and (e) investigate through survey research the beliefs and attitudes of association leadership toward ethical code issues. The content analysis and survey research results have implications for association leadership, its membership, public policy makers, the general public and for future research.